2010
DOI: 10.1159/000315439
|View full text |Cite
|
Sign up to set email alerts
|

A Symptom-Specific Analysis of the Effect of High-Frequency Left or Low-Frequency Right Transcranial Magnetic Stimulation over the Dorsolateral Prefrontal Cortex in Major Depression

Abstract: Background: We have investigated the efficacy of high-frequency left (HFL) versus low-frequency right (LFR) repetitive transcranial magnetic stimulation (rTMS) in depression, focusing on specific symptoms as possible predictors of outcome for these two different types of stimulation. Method: Seventy-four outpatients with a major depressive episode treated with an adequate antidepressant dosage for at least 4 weeks were included in our study and randomly assigned to two different groups: HFL or LFR rTMS. The Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 107 publications
2
20
0
1
Order By: Relevance
“…The combination of HF-rTMS and LF-rTMS could potentially enhance treatment response in MD in a number of ways. For example, it is possible that some patients have left-side treatment-responsive MD and some have right-side treatment-responsive MD (Rossini et al 2010). Therefore, it is conceivable that offering both treatments to all patients can maximize the likelihood of clinical improvement in any individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of HF-rTMS and LF-rTMS could potentially enhance treatment response in MD in a number of ways. For example, it is possible that some patients have left-side treatment-responsive MD and some have right-side treatment-responsive MD (Rossini et al 2010). Therefore, it is conceivable that offering both treatments to all patients can maximize the likelihood of clinical improvement in any individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…13 Studies comparing HFL-rTMS and LFR-rTMS have found equivalent response rates with the 2 treatments. [14][15][16] Thus, combining these 2 treatments may result in…”
Section: Introductionmentioning
confidence: 99%
“…rTMS is administered using a high-field (w1.5 T) electromagnet, with the best established protocols targeting the left dorsolateral prefrontal cortex (DLPFC) at frequencies of 10e20 Hz [2,4], or the right DLPFC at a frequency of 1 Hz [8,9]. The optimal intensity, brain area, and frequency of stimulation have not been established through controlled studies [10].…”
Section: Introductionmentioning
confidence: 99%